The Role of Parents in Children's Education in the Cartoon Film Umar and Hana from an Islamic Education Perspective - Miranda, Mega; Tabrani, Akhmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The cartoon film "Umar and Hana" is an effective medium in instilling Islamic moral and ethical values in children. This research aims to explore the role of parents in integrating Islamic teachings taken from the cartoon film "Umar and Hana" into children's daily lives. This research method uses Study Literature Review (SLR). The research results explain that the role of parents in guiding, being a role model, and creating a positive learning environment plays a key role in shaping children's character. Open discussion and integration of Islamic values in children's daily lives are important strategies in facing challenges and applying Islamic teachings from this film. Special episodes, such as "Halal Ke," "Natural Heroes," "Our Qibla," "A Surprise for Papa," and “Wash Your Hands First,” provide specific teachings about Allah's creation, cleanliness, natural beauty, Qibla, and filial piety to parents. This film, with the active involvement of parents, is not only a source of entertainment but also a tool for forming character and moral values in children's daily lives.